O sagrado e o profano no consumo ritualístico de casamentos cristãos - Hofmann, Laiza Fernanda dos Santos (2015)
The consumption of the sacred can be recognized in different contexts and their range allows many possibilities in the study of consumer behavior. The theory of the sacred consumption points to the concept of the sacred, in environments that go beyond the religious. The theory understands man, as a being that even seeking the profane, in the sense of common, has behaviors of consecration that are intrinsic to its nature. The consumption of the sacred has always been present in human daily life. Artifacts, places and even people are needed for sacred rituals. The idea of sacredness had been studied by the science of religion for some time already, until the late 1980s when Belk, Sherry and Wallendorf (1989) began to pursue studies using science of religion concepts to applied to their studies of consumer behavior. Through theoretical and empirical studies the authors proposed the theory of sacred consumption. However, few studies, including research by the authors, focuses on natural sacred contemporary environments, although it is mentioned the possibility of this studies area. This search dissertation, seeks to combine the theory of sacred consumption proposed by Sherry Belk and Wallendorf (1989) to the study of consumption rituals by Rook (2007), analyzing the marriage ritual in different Christian denominations. Pursuing this, priests and pastors were interviewed. Ecclesiastical documents on marriage ritual were also analyzed as well as observations from premarital counseling to understand these communities´ positions regarding nuptial rituals. Semi-structured and non-structured interviews were made with brides, grooms and newlyweds to understand how they sacredise and desacredise the marriage rituals. It was noticed, that the couples´ church influenced them for the construction of rituals and that the behavior of sacredising and desacredising are closely linked to the beliefs,doctrines and forms of worship practiced by their religious community. This study, among other things, helps in expanding the understanding of the concept of the sacred in contemporary religious environments and provides material for the construction and improvement of better services and products to the ritual in different Christian contexts.